Breeding medicinal plant, periwinkle [Catharanthus roseus (L) G. Don]: a review. Issue 4 (2nd May 2016) - Kulkarni, R. N.; Baskaran, K.; Jhang, Tripta
Abstract: Periwinkle [ Catharanthus roseus (L) G. Don] has become one of the very extensively investigated medicinal plants after the discovery of two powerful anti-cancer alkaloids, vinblastine and vincristine, in its leaves more than 50 years ago. These alkaloidal drugs are still in clinical use. Also, periwinkle is still the only source of these alkaloids and their precursors, catharanthine and vindoline. Low concentrations of these alkaloids in the plant and, therefore, high costs of their extraction have led to tremendous efforts towards understanding their biosynthesis and exploration of alternate ways of their production such as, chemical synthesis, cell, tissue and hairy root cultures, and metabolic engineering of heterologous organisms. Literature on this plant is quite voluminous, with an average of about 80 publications per year during last three decades (1985–2015). Nearly 60% of these publications are on physiology, biochemistry, cell and tissue culture, phytochemistry, metabolic and genetic engineering aspects. In spite of these efforts, an economically viable alternative to field-grown periwinkle plants as a source of these alkaloids has not yet been found. Biosynthesis of C. roseus alkaloids is a complex process involving many genes, enzymes, regulators, inter- and intra-cellular transporters, cell types, organelles and tissues and its current understanding is still considered to be incomplete to produce C. roseus alkaloids through metabolic engineering/synthetic biology. Till such time, breeding periwinkle varieties with higher concentrations of anti-cancer alkaloids for cultivation can be an alternate approach to meet the demand for these alkaloids and reduce their costs. While literature on cell and tissue culture, phytochemistry, metabolic and genetic engineering aspects of periwinkle has been reviewed periodically, crop production and plant breeding aspects have received little attention. In this paper, an attempt has been made to bring together published information on genetics and breeding of periwinkle as a medicinal plant. Some probable constraints which may have hindered taking up periwinkle breeding are identified. Initially, quite a few attempts have been made at genetic improvement of periwinkle through induced polyploidy, and subsequently through induced mutagenesis. Mutations, both natural and induced, provide a valuable resource for use in breeding and in functional and reverse genomics research. It is only during last 6–7 years, genetic diversity has been assessed using molecular markers and very recently molecular markers have been identified for marker-assisted selection for alkaloid yield.